Pengaruh Inflasi Dan Jumlah Uang Beredar Terhadap Profitabilitas Perbankan Syariah Di Indonesia - Utami, Mega; Sihotang, Mutiah Khaira (Universitas Labuhanbatu, 2024)
This research was conducted to determine the effect of inflation and the money supply on the profit of Islamic banking in Indonesia. The population in this study is all data on the financial statements of Islamic Commercial Banks (BUS) That have been published by the Financial Services Authority (OJK) in islamic Banking Stasticts (SPS) and all data from Bank Indonesia (BI). The samples in this study are Inflation and Money Supply data from BI monthly reports for 5 years and Profitability data from BUS monthly reports for 5 years, from January 2018 to December 2022 released by OJK in the SPS. The analytical method used is quantitative analysis. The results of the hypothesis test showed that the significant value for the influence of inflation (X1) and the Money Supply (X2) simultaneously on ROA (Y) was 0.000 < 0.05 and the Fcount value was 33.777 > F table 3.16. So it can be concluded that Ha 1 Â is accepted, which means there is an effect of inflation (X1) and the Money Supply (X2) simultaneously o ROA (Y).